(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Nursing performance remains a decisive determinant of clinical reliability in settings characterised by fluctuating acuity and documentation density. This study aimed to examine an integrative model of education, role adaptation, and work ecology in understanding nursing performance within contemporary clinical settings. A cross-sectional approach was applied to thirty-three respondents using validated self-administered questionnaires and multiple regression analysis. Correlation analysis indicated that role adaptation was strongly associated with clinical performance (r = 0.85), while work ecology demonstrated a similarly high association (r = 0.74). Regression findings confirmed that both variables jointly accounted for substantial variance in nursing performance (adjusted R² = 0.81), with role adaptation (β = 0.59, p <0.001) and work ecology (β = 0.45, p <0.001) emerging as significant predictive contributors. These findings suggest that nursing performance is stabilised not solely by individual adaptive judgement, but through its synchronisation with educational grounding and environmental clarity. The study positions nursing performance as a co-regulated outcome of education, adaptive cognition, and work ecological structure at the time of observation.